2009
DOI: 10.2169/internalmedicine.48.2414
|View full text |Cite
|
Sign up to set email alerts
|

Notable Difference between the Development of Vertebral Fracture and Osteonecrosis of the Femoral Head in Patients Treated with High-dose Glucocorticoids for Systemic Rheumatic Diseases

Abstract: Objective Vertebral fracture (VF) and osteonecrosis of the femoral head (OFH) are serious concerns in patients with rheumatic diseases treated with high-dose glucocorticoids (GCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Furthermore, the above theories do not clearly explain the occurrence of osteocyte necrosis as no cell swelling and inflammation accompany the characteristic necrosis of SANFH. Steroidal hormones, such as glucocorticoids, have been demonstrated to induce apoptosis (17). They reduce the number of osteocytes by promoting the apoptosis of osteoblasts and osteocytes, and they also affect the function of osteoblasts, retard osteogenesis and induce cell apoptosis, which results in bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the above theories do not clearly explain the occurrence of osteocyte necrosis as no cell swelling and inflammation accompany the characteristic necrosis of SANFH. Steroidal hormones, such as glucocorticoids, have been demonstrated to induce apoptosis (17). They reduce the number of osteocytes by promoting the apoptosis of osteoblasts and osteocytes, and they also affect the function of osteoblasts, retard osteogenesis and induce cell apoptosis, which results in bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…The comparative study of Kameda et al. presented that the progression of ONFH relied on the response to a high dose of GC therapy and a decrease in the bone mineral density value in the 1st year [ 24 ]. Saito et al.…”
Section: The Etiology and Pathogenesis Of Onfhmentioning
confidence: 99%
“…The comparative study of Kameda et al . [ 6 ] showed that the development of ONFH depended on the response to a high dose of corticosteroid therapy and a decrease in the bone mineral density value in the 1 st year. The prospective study of Shigemura et al .…”
Section: Etection In the E Arlier mentioning
confidence: 99%